ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DENGAN MENGGUNAKAN INCOME STATEMENT APPROACH DAN VALUE ADDED APPROACH - Muchamad Fauzi (STIE Pelita Nusantara Semarang, 2012)
This study was to assess the financial performance of Islamic banking if calculated with the income approach and the value-added and to obtain empirical evidence on differences in the financial performance of Islamic banking which is calculated by the value-added approach and views of ROA, ROE, the ratio between the total net income with total earning assets, NPM and ROA. The type of research is quantitative, its population is Islamic Bank’s financial statements which are prepared in the form of annual consist of a balance sheet, income statement, statement of quality aktiva productive, and notes to the consolidated financial statements using the sample period from 2003 - 2010, use the analysis descriptive statistics and different test of t-test. The results of this research are: 1) the financial performance represented by ROA, ROE, the ratio of net income to earning assets, and NPM in 2003-2010 showed the income statement approach and Value added approach, there are significant differences. Although quantitatively the amount of the four ratios approach the income statement under Value added approach. 2) financial performance represented ROA ratio in 2003-2010 showed the income statement approach and Value added approach there is no significant difference. This is because the operating income and operating expenses Value added approach is still treated as the income statement approach. 3) The overall rate of Islamic banking profitability as measured by using the income statement approach and Value added approach have significant differences. According to the research results obtained by the ratio of the amount of income statement approach is lower than the Value added approach 4) There is a difference between the income statement approach and Value added approach, the VAA prefer the principle of fairness in the distribution of added value to the owners of capital, employees, creditors, and government. Thus, in this study were obtained value (profit) is higher compared to the profit obtained under the income statement approach.